Vocaburaries food in Thai literature : Relationship on Language and Thai Culture Relationship on Language and Thai Culture - Prayyong, Vichuda (Mahachula Academic Journal, 2026)
Academic Article titled ‘Food Vocabulary in Thai Literature:Relationship on Language and Thai Culture This academic article aims to study the author investigates Thai literatures from the Sukhothai, Ayutthaya, Thonburi, and Rattanakosin periods, employing purposive sampling from the following works: (๑) Traiphum Phra Ruang, (2) Nirat Phraya Mahanuphap’s Journey to China, (3) The Verse of food and dessert by King Rama ii (4) Phra Aphai Mani, and (5) Rampan Pilap. Food vocabulary in these texts is categorized and analyzed based on semantic criteria and the etymology of food names, as defined in the Royal Institute Dictionary (20๑๑). The study further draws upon theoretical perspectives on linguistic and cultural reflection proposed by Phraya Anuman Rajadhon and the Ministry of Culture.From the selected corpus, the author identifies 15 food-related lexical items. These include entries from Nirat Phraya Mahanuphap’s Journey to China (Thonburi period) and four Rattanakosin-era works: Khun Chang Khun Phaen The Verse of food and dessert by King Rama ii, , Phra Aphai Mani, and Rampan Pilap. The classification reveals: 6 terms related to everyday life, 5 terms associated with ritual practices, 3 loanwords from foreign languages, and ๑ term of regional dialectal origin. The prevalence of vocabulary related to daily life reflects the simplicity of traditional Thai ways of living, closely tied to the abundance of natural resources. In addition, food vocabulary commonly used in traditional ceremonies often carries auspicious meanings, thereby demonstrating the close interrelationship between language and culture. Moreover, food names such as Tom Yam (Kung), which has been inscribed as an element of UNESCO’s Intangible Cultural Heritage. Food vocabulary derived from foreign languages and regional dialects reflects the processes of cultural interaction and exchange between Thailand and other societies. The study of food vocabulary in Thai literature thus serves as a valuable Relationship on Language and Thai Culture across different historical periods.